Evidence for nodal superconductivity in a layered compound Ta4Pd3Te16. (9th January 2018) - Pang, Guiming; Smidman, Michael; Jiao, Wenhe; Jiao, Lin; Weng, Zongfa; Jiang, Wenbing; Guo, Chunyu; Chen, Ye; Cao, Guanghan; Yuan, Huiqiu
Abstract: We report an investigation of the London penetration depth Δ λ ( T ) on single crystals of the layered superconductor Ta4 Pd3 Te16, where the crystal structure has quasi-one-dimensional characteristics. A linear temperature dependence of Δ λ ( T ) is observed for T ≪ T c, in contrast to the exponential behavior of fully gapped superconductors. This indicates the existence of line nodes in the superconducting energy gap. A detailed analysis shows that the normalized superfluid density ρ s ( T ), which is converted from Δ λ ( T ), can be well described by a multigap scenario, with nodes in one of the superconducting gaps, providing clear evidence for nodal superconductivity in Ta4 Pd3 Te16 .